Agricultural uses of occult precipitation 1 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Pest, diseases, and nutritional disorders of the common bean in Africa: a field guide by D J Allen J K O Ampofo and C S Worthmann 1996 132pp ISBN 958 9439 55 1